Undergraduate nursing student mentors' experiences of peer mentoring in Korea: A qualitative analysis. (April 2017) - Won, Mi-Ra; Choi, Yun-Jung
Abstract: Background: Although mentoring involves the achievement of a mutual relationship between mentors and mentees, most studies have focused on the effects of mentoring on the mentees rather than that on the mentors, which necessitates the need to identify mentors' experiences to provide original resources for mentoring. Objectives: The purpose of this study was to explore the mentoring experience of nursing students who participated as mentors in a mentoring learning program, to offer evidence-based resources for nursing educators to develop mentoring programs and to use mentorship as an educational method. Design: A qualitative content analysis of transcribed focus groups was conducted to describe and explore the undergraduate nursing students' mentoring experiences. Setting: This study was conducted in two nursing schools in South Korea. Participants: Fifteen student mentors from the peer mentoring program participated in the present study. They were aged between 21 and 24 years, and 87% of the participants were female. Methods: The experiences of the mentors were explored through focus groups, and the collected data were analyzed by content analysis. Results: The mentors' experiences could be summarized by the core theme, " Self-growth as a leader, " consisting of the following themes: taking pride, guiding mentees, coping with conflicts, and building leadership . Conclusion: The themes and codes derived from mentors' experiences would provide evidence-based guidelines and resources for nursing educators and professionals in related disciplines regarding successful peer mentoring, which could facilitate self-growth and foster the development of leadership skills in undergraduate students. Highlights: The peer mentoring program is beneficial for not only mentees but also mentors in nursing education. The student mentors may have experiences of " Taking pride, Guiding mentees, Coping with conflicts, and Building leadership ". Through the peer mentoring program, the student mentors would have qualitative development of " Self-growth as a leader ".